Determination of optimal gamma radiation dose for mutation breeding in ’Sabz’ fig (Ficus carica L.) cuttings based on radiosensitivity and phenotypic changes - Ali Akbar Ghasemi-Soloklui; Mojtaba Kordrostami; Moslem Jafari (PLoS ONE, 2025)
The dried fig cv. Sabz of Iran, distinguishes out among the several fig cultivars for its unique characteristics and excellent properties. The aims to this study were 1) Carefully monitoring the resulting phenotypic changes in growth patterns, leaf morphology, shoot traits, root characteristics, and other relevant traits after irradiated with different gamma rays; 2) Investigating the LD25, 50, 75 and GR25, 50, 75 values at different gamma radiation doses for chose optimum dose. According to our results, the LD50 was 70 Gy, while the LD25 and LD75 were approximately 48 and 95 Gy, respectively. Data analysis revealed that higher doses, ranging from 50 to 90 Gy, led to a reduction in leaf area for fig hardwood cuttings compared to those exposed to lower doses of gamma irradiation (10, 20, 30, and 40 Gy). In fig cuttings, the plant height gradually decreased in line with increasing irradiation doses up to 60 Gy. Among the root traits, root number was particularly influenced by higher radiation doses. On other hand, when fig cuttings were exposed to a 40 Gy radiation dosage, the average root count dropped by 50%. However, when fig cuttings were subjected to a 90 Gy radiation dose, the average root count surged by 90.7% in comparison to the control treatment. Additionally, the GR50 values were 63 Gy for internode length, 67 Gy for leaf area and 56 Gy for plant height and aerial biomass. However, the GR50 values for root number, root volume, and root biomass were 46 Gy, 57 Gy, and 51 Gy, respectively. An analysis based on the GR25, GR50, and GR75 values indicated that plant height, aerial biomass and root biomass exhibited greater sensitivity to radioactivity in comparison to other plant portions of the fig. According to the biological responses in the ‘Sabz’ fig, 60 Gy of gamma radiation is a suitable dose for initial mutagenesis studies.